IGSF9-targeted therapy inhibits the progression of acute myeloid leukemia - Lijun Hui; Jing Xiao; Zhiling Zhao; Juan Zhang; Huiwen Luan; Jiashen Zhang; Yuxiao Sun; Xianhui Meng; Hongying Wang; Chunling Li; Fangmin Li; Shuhao Ji; et al. (Blood Advances)
Abstract: Previously, we reported that targeting immunoglobulin superfamily member 9 (IGSF9) could enhance antitumor T-cell activity and sensitivity to anti–PD-1 immunotherapy, although the detailed mechanism remains unclear. In this study, we find that, similar to the regulation of PD-L1 expression, interferon gamma (IFN-γ) also induces the expression of IGSF9 in acute myeloid leukemia (AML). The small interfering RNA specifically targeting JAK1 and a STAT1 inhibitor blocking IFN-γ signal pathway significantly inhibit the expression of IGSF9 and PD-L1. As a tumor-specific immune checkpoint molecule, IGSF9 plays a significant role in promoting tumor escape. The induction of both PD-L1 and IGSF9 by IFN-γ in the tumor microenvironment explains why IGSF9 is highly expressed in tumors and tumor-infiltrating immune cells. This induction also underpins the strong synergistic effects when combining anti-IGSF9 and anti–PD-1 therapies. Additionally, IGSF9 also mediates the extramedullary infiltration of AML cells, which can be inhibited by depletion of IGSF9 or anti-IGSF9. The binding epitopes of anti-IGSF9 are located within the immunoglobulin G2 and fibronectin type-III-2 domains of IGSF9. Based on these findings, we develop an antibody-drug conjugate (ADC) targeting IGSF9 (anti–IGSF9-linker-DXd). This ADC exhibits 99.7% purity, and primarily exists in monomeric form, demonstrating excellent homogeneity (drug-to-antibody ratio, 8-10) and specificity. Anti–IGSF9-linker-DXd effectively kills IGSF9-positive tumor cells and exhibits a potent bystander effect. In vivo, anti–IGSF9-linker-DXd almost completely eliminates early- and mid-stage tumors and significantly inhibits the progression of advanced tumors. In summary, our findings underscore the potential of IGSF9 as a novel therapeutic target for AML treatment, highlighting its role in disease progression and the efficacy of targeted therapies.